Lingam inside the Garbagriha at Walkeshwar Temple - Ghosh, Ayan (2023)
The lingam worshipped in the garbagriha of Walkeshwar Temple is said to be swayambhu (self-manifested). The lingam has a brass kavach (armor) and is protected within the coil of a brass Naga (serpent). It is believed that this lingam was brought from Varanasi by Lakshman, hence Walkeshwar is also referred to as Lakshmaneswar.